Pierre Menard, author of Don Quixote: a reflection on the practice of the textual comment - Vinatea Recoba, Martina (2010)
Practice of textual comments has been mainly developed within the theoreticalsphere. Jorge Luis Borges, in its short story Pierre Menard, author of Quijote,reflects on the sense of the text from the perspective of the reader. In this pieceof work, Borges answers the question about the ideal reader. Pierre Menardpersonifies such reader, who, at first, to strictly comply with his role as acompetent reader, tries to become assimilated with the text; and later discoversthat the best way to accomplish his purpose is to grab hold of it, that is, reachthe text from his own experiences. This is the ideal reader of all times, he who acknowledges the work, the author, and its circumstances, and, this informationworks as his baggage to take hold of his own experience, to withdraw thesense of the text.